Force decay and deformation of colored and gray elastomeric ligatures - Yu, Maria Irene G.
The purpose of this study was to evaluate force decay, permanent deformation and the relationship between the ligature and the force, of commercially available colored (blue) and gray elastomeric ligatures (GAC, ORMCO, UNITEK) in a simulated oral environment. The initial wall thickness (WT), inside diameter (ID), outside diameter (OD), and force levels of each ligature were measured. Three of the four test groups were stretched over stainless steel dowels with a circumference approximating of a large orthodontic bracket. Test group 1 was kept at room temperature and humidity for 28 days and Test group 2 in natural saliva at 37?C for 28 days. The residual forces and dimensional changes were measured. The third test group was placed in natural saliva at 37?C, and force levels recorded at initial, 24 hours, 7 days, 14 days, 21 days, and 28 days. Test group 4 of unstretched samples were placed in natural saliva at 37?C for 28 days to evaluate dimensional changes due solely to water sorption. The results revealed the following: (1) Moisture and heat influences force delivery of elastomeric ligatures. These modules exhibit rapid force loss (45.82to 70.40) for gray ligatures and 56.26to 69.68for blue ligatures), and deform permanently; (2) The GAC elastomeric ligatures, in a simulated oral environment, showed the least mean percentage of dimensional changes and least mean percentage of force loss when compared to the ORMCO and UNITEK ligatures; (3) Blue elastomeric ligatures decay more than the gray ligatures by 6.68, so the introduction of the coloring agent must have had an effect on force delivery properties of the ligatures and, (4) It is only during leveling and aligning or the first phase of orthodontic treatment that these elastomeric ligatures are very useful. Due to the rapid loss of force and permanent deformation exhibited by the ligatures, these products are not practical during rotatinal and torquing movements. These procedures require complete seating of the arch wire in the bracket slots in order to achieve the desired movements.